Hexadecenoic Fatty Acid Isomers in Human Blood Lipids and Their Relevance for the Interpretation of Lipidomic Profiles - Sansone, Anna; Tolika, Evanthia; Louka, Maria; Sunda, Valentina; Deplano, Simone; Melchiorre, Michele; Anagnostopoulos, Dimitrios; Chatgilialoglu, Chryssostomos; Formisano, Cesare; Di Micco, Rosa; Faraone Mennella, Maria Rosaria; Ferreri, Carla (PLOS ONE, 2016)
Monounsaturated fatty acids (MUFA) are emerging health biomarkers, and in particular the ratio between palmitoleic acid (9cis-16:1) and palmitic acid (16:0) affords the delta-9 desaturase index that is increased in obesity. Recently, other positional and geometrical MUFA isomers belonging to the hexadecenoic family (C16 MUFA) were found in circulating lipids, such as sapienic acid (6cis-16:1), palmitelaidic acid (9trans-16:1) and 6trans-16:1. In this work we report: i) the identification of sapienic acid as component of human erythrocyte membrane phospholipids with significant increase in morbidly obese patients (n = 50) compared with age-matched lean controls (n = 50); and ii) the first comparison of erythrocyte membrane phospholipids (PL) and plasma cholesteryl esters (CE) in morbidly obese patients highlighting that some of their fatty acid levels have opposite trends: increases of both palmitic and sapienic acids with the decrease of linoleic acid (9cis,12cis-18:2, omega-6) in red blood cell (RBC) membrane PL were reversed in plasma CE, whereas the increase of palmitoleic acid was similar in both lipid species. Consequentially, desaturase enzymatic indexes gave different results, depending on the lipid class used for the fatty acid content. The fatty acid profile of morbidly obese subjects also showed significant increases of stearic acid (C18:0) and C20 omega-6, as well as decreases of oleic acid (9cis-18:1) and docosahexaenoic acid (C22:6 omega-3) as compared with lean healthy controls. Trans monounsaturated and polyunsaturated fatty acids were also measured and found significantly increased in both lipid classes of morbidly obese subjects. These results highlight the C16 MUFA isomers as emerging metabolic marker provided that the assignment of the double bond position and geometry is correctly performed, thus identifying the corresponding lipidomic pathway. Since RBC membrane PL and plasma CE have different fatty acid trends, caution must also be used in the choice of lipid species for the interpretation of lipidomic profiles.